Adaptasi dan Validasi Skala Cyber-Aggression Questionnaire for Adolescents - Nur Amalia Hamida; Lu'luk Syahrul Kamal; Nur Rahmat Laba; Aisha Al Mascaty; Niken Nahesti (Journal Psikologi Forensik Indonesia, 2023)
The interactions of teenagers and early adults have on social media are not always in positive way. Some of them carry out various negative behaviors as a form of aggressiveness in the online platform. This research aims to adapt and validate the Cyber-Aggression Questionnaire for Adolescents scale developed by Gracia, et al (2016). The cyber aggression measuring tool will aim to measure the level of aggressive behavior in the online platform carried out by individuals in adolescents and early adults. This research was conducted online with teenagers and early adults aged 13 - 24 years in Indonesia. There were 430 participants, consisting of 157 men and 273 women. The results of confirmatory factor analysis (CFA) showed good model fit (CFI = .974, TLI = .931, RMSEA = .0489). In addition, the results showed that the 12-item cyber aggression scale had quite good internal consistency (α = .786). Multigroup analysis showed that the model had invariance across male and female samples (gender).